2022
DOI: 10.1186/s12967-022-03568-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and methylation profiles show the involvement of POMC in primary hyperparathyroidsm

Abstract: Primary hyperparathyroidism (PHPT) is mainly caused by parathyroid adenoma, which produces excess parathyroid hormones. Its pathogenic mechanisms have not yet been fully understood. To investigate the mechanism in the pathogenesis of PHPT, the transcriptome and genome-wide DNA methylation profiles of parathyroid adenoma were analyzed. The candidate genes that may be involved in the PHPT were verified via qRT-PCR, immunohistochemistry, western blot, and methylation-specific PCR. A total of 1650 differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Consistent with our findings, a previous study has reported the down-regulation of POMC in parathyroid adenomas samples. 39 Our single-cell study provides further evidence that the downregulation of POMC expression is located in PTH + cells. Our data also highlighted CD4, CD226, ART5 and GPR32, which have not been reported, as suggestive biomarkers that were potentially involved in adenoma initiation and progression.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with our findings, a previous study has reported the down-regulation of POMC in parathyroid adenomas samples. 39 Our single-cell study provides further evidence that the downregulation of POMC expression is located in PTH + cells. Our data also highlighted CD4, CD226, ART5 and GPR32, which have not been reported, as suggestive biomarkers that were potentially involved in adenoma initiation and progression.…”
Section: Discussionsupporting
confidence: 58%
“…Interpretation of our study is further hindered by (a) the partial heterogeneity of the groups studied (ECT patients were older than control subjects), (b) conflicting results regarding NR3C1m in the literature, (c) the lack of data complementary to our DNAm analysis (neither mRNA nor protein expression was evaluated), (d) the very small differences in methylation levels, (e) the fact that DNAm between brain and periphery may greatly differ, and (f) the weak association between DNAm and gene expression in general. Regarding the latter (f), however, recent studies found that the DNAm of NR3C1-1F and POMC were inversely correlated with NR3C1 and POMC (and thus ACTH), respectively [44][45][46].…”
Section: Discussionmentioning
confidence: 95%
“…Hypermethylation of CpG islands and low expression of the POMC gene were found in parathyroid adenoma tissues compared with normal parathyroid tissues, suggesting that hypermethylation of the POMC gene may be associated with the development of parathyroid adenomas. [ 13 ] This finding provides a new approach for investigating the pathogenesis of parathyroid adenomas by examining other endocrine axes.…”
mentioning
confidence: 99%